Improving outcomes with integrated care of patients with atrial fibrillation and multimorbidity using mobile health technology: a report from the mAFA II trial. (14th October 2021) - Guo, Y; Lip, G Y H; ,
Abstract: Background: The mAFA-II trial is a prospective cluster randomized trial which showed that when compared to usual care, integrated care in patients with atrial fibrillation (AF) using mobile health (mHealth) technology implementing the ABC pathway: "A" Anticoagulation/Avoid stroke; "B" Better symptom control; "C" Cardiovascular disease management) was associated with a significant reduction in the "composite clinical outcome" of stroke/thromboembolism, all-cause death and rehospitalization. Multimorbidity (MM, defined as ≥2 chronic long-term conditions) is common in elderly AF patients and the impact of integrated care on outcomes is uncertain. Objective: To evaluate whether implementation of mHealth technology-supported integrated ABC Pathway, would reduce AF-related adverse events in patients with MM. Methods: We analysed the MM subset of AF patients (≥2 comorbidities of hypertension, coronary artery disease, heart failure (HF), cardiomyopathy, peripheral arterial disease, diabetes mellitus liver/renal dysfunction, pulmonary disease, prior stroke, etc.) participating in the mAFA II trial between June 1, 2018 and April 1, 2020 across 40 centers in China. We used Cox proportional hazard modelling after adjusting for cluster effect and baseline risk factors. Results: There were 833 patients (mean age 72.0 years, 33.4% female) with MM allocated to intervention (ABC pathway) with mean follow-up of 419 (SD 257) days; and 1057 patients (mean age 72.8 years, 41.9% female) with MM were allocated to usual care with mean follow-up of 457 (SD 154) days. Compared to usual care, the composite outcome of stroke/thromboembolism, all-cause death and rehospitalization was significantly reduced with the mAFA (ABC pathway) intervention (Hazard Ratio, HR, 0.37, 95% CI: 0.26–0.53, p<0.001), as was hospitalisations (HR 0.42, 95% CI: 0.27–0.64). For the A criterion, rates of thromboembolism were lower with mAFA intervention (0.5% vs 2.9%; HR 0.17, 95% CI: 0.05–0.51, P=0.002), with no difference in bleeding. For the C criterion, rates of the occurrence of acute coronary syndrome, HF, uncontrolled blood pressure, etc. during the follow-up were lower with mAFA intervention (3.2% vs. 13.7%, HR 0.29, 95% CI: 0.19–0.45, P<0.001). The B criterion was not associated with a significant reduction in the composite outcome. Subgroup analyses, by age, prior stroke, sex demonstrated consistently lower HRs for the primary composite outcome and rehospitalization for patients allocated to mAFA intervention when compared with patients receiving usual care (all p<0.05 vs. usual care) Conclusion: mHealth technology based integrated care approach, facilitating the ABC pathway, reducing the clinical adverse events in elderly AF patients with multimorbidity, compared to usual care. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Natural Science Foundation of China (No. 8147413)